Bukholderia strains promote Mimosa spp. growth but not Macroptilium atropurpureum - Kaliane Sírio Araújo (Revista Ciência Agronômica, 2017)
The aim of this study was to evaluate the relationship and symbiotic efficiency of 14 strains of Burkholderia isolated from rupestrian grasslands, using M. atropurpureum and Mimosa tenuiflora as trap plants, with the species M. atropurpureum,Mimosa bimucronata and M. foliolosa. For the nodulation and symbiotic efficiency test inM. atropurpureum, long-neck bottles containing nutrient solution were used. The experiments with Mimosa spp. were carried out in tubes containing vermiculite (160 cm3) and sand (80 cm3) (2:1). The parameters under evaluation were number of nodules, nodules dry matter production, shoots dry matter, roots dry matter, and total dry matter production for all the species analyzed; and plant height, diameter, and the Dickson quality index for Mimosa species. Of the 14 tested strains, two nodulated M. atropurpureum; however, they were ineffective in promoting plant growth. All the tested strains established symbiosis with M. bimucronata, and 12 strains nodulated M. foliolosa. Of these, six promoted growth in M. bimucronata, and seven presented symbiotic efficiency in M. foliolosa. The strains UFLA 01-739, UFLA 01-748 and UFLA 01-751, isolated from M. tenuiflora, and UFLA 04-260 and UFLA 04-405, isolated from M. atropurpureum, stood out as potential inoculants for the Mimosa species evaluated in this study.